(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores methods for developing reading comprehension skills in early grade students, with a focus on transitioning from technical reading to meaningful text understanding. It analyzes the theoretical foundations of reading comprehension, the role of phonics in decoding, and the importance of vocabulary and background knowledge. Special emphasis is placed on pedagogical strategies and practical techniques that support the development of meaningful reading. The article provides specific methodological recommendations for primary school teachers, including pre-reading, during-reading, and post-reading strategies, individualized instruction, and the fostering of reading motivation. It aims to improve the effectiveness of teaching reading at the primary level and to enhance students’ functional literacy.